Dampak Pengembangan Karir Dan Insentif Terhadap Kepuasan Kerja Karyawan TU SMP Kecamatan Guguak - Suhatri, Desnina (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This article was compiled based on research conducted with the aim of knowing the effect of Career Development (X1) and Incentives (X2) variables on Employee Job Satisfaction. The population of this study were all 45 employees of the Administrative Section (TU) in the Gugua District Junior High School with a sampling technique using a saturated sampling technique. Collecting data using a survey with a questionnaire tool distributed to the research respondents. The analytical tool used is multiple linear regression with hypothesis testing which includes t test, F test and coefficient of determination test (R2). The results of the research that has been carried out are known that the Career Development variable (X1) has a positive and significant effect on Employee Job Satisfaction. While the Incentive variable has a positive and insignificant effect on Employee Job Satisfaction.